Astronomical Verification of the Prophet Muhammad’s Birth Date: Revisiting the Surakarta Palace Senin Pon Tradition - Purwanto Purwanto; Sayful Mujab (Al-Hilal: Journal of Islamic Astronomy, 2026)
The Surakarta Palace preserves a long-standing tradition that associates the birth of Prophet Muhammad with Monday Pon (Senin Pon) in the Dal year cycle, forming the basis of the Grebeg Mulud commemoration. Despite its cultural significance, the historical and astronomical foundations of this tradition have received limited scholarly attention. This study examines the relationship between the Surakarta Palace Senin Pon tradition, classical Islamic historiography, and astronomical chronology. Employing a qualitative library research design, the study integrates historiographical analysis, cultural-textual analysis of Javanese calendrical manuscripts, and astronomical reconstruction based on contemporary ephemeris calculations. The findings indicate that while the Monday birth of the Prophet is widely supported by classical sources, the reconstructed chronology of Rabīʿ al-Awwal in the Year of the Elephant suggests that Monday corresponded more plausibly to the 10th rather than the 12th of Rabīʿ al-Awwal. Nevertheless, the persistence of the Senin Pon tradition reflects the role of the Javanese calendar in preserving sacred historical memory through ritual continuity and cultural transmission. This study contributes to Islamic astronomy by integrating historical astronomy, Islamic historiography, and Javanese calendrical traditions within a single analytical framework.